2022
DOI: 10.3390/nu14071429
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Phytochemical Index and Overweight/Obesity: A Meta-Analysis

Abstract: Some studies suggest that a higher phytochemical index (PI) is associated with a lower risk of overweight/obesity. This meta-analysis is performed to summarize published studies on the relationship of PI and the risk of overweight/obesity. We searched on PubMed, Cochrane Library and Web of Science from the inception dates to February 2022. The random-effect model was used based on heterogeneity. Meta-regression was used to explore potential sources of between-study heterogeneity. Publication bias was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…To our knowledge, no previous study has assessed the association between DPI score and CRC. Regarding chronic disease, meta-analyses have revealed that higher adherence to DPI is associated with a lower risk of overweight/obesity [ 34 ], hypertension, hypertriglyceridemia, and metabolic syndrome [ 35 ]. In our study, participants in the highest DPI had a higher intake of whole grains, fruits, vegetables, fish, and poultry and a lower intake of refined grains than the lowest tertile.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no previous study has assessed the association between DPI score and CRC. Regarding chronic disease, meta-analyses have revealed that higher adherence to DPI is associated with a lower risk of overweight/obesity [ 34 ], hypertension, hypertriglyceridemia, and metabolic syndrome [ 35 ]. In our study, participants in the highest DPI had a higher intake of whole grains, fruits, vegetables, fish, and poultry and a lower intake of refined grains than the lowest tertile.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have shown that higher PI is associated with a reduction in inflammation, hypertension, diabetes, metabolic syndrome, and stroke [ 21 , 23 , 24 , 25 , 26 ]. A recent meta-analysis confirmed that PI is inversely associated with obesity and overweight, with higher PI levels being observed in groups with lower rates of obesity and overweight [ 27 ]. Given the promising findings associated with PI, it is possible to use this index to examine the overall effects of phytochemical intake on bone health.…”
Section: Introductionmentioning
confidence: 99%
“…The dietary phytochemical index (DPI) is defined as the percentage of dietary calories derived from foods rich in phytochemicals [20]; a higher DPI is strongly associated with a lower prevalence of overweight/obesity [21][22][23], cardiovascular disease, metabolic syndrome [24], and cancer [20]. A meta-analysis revealed that a lower DPI decreases the risk of overweight/obesity by 19% (95% confidence interval [8]: 0.74-0.90) [21]. However, the results demonstrated significant heterogeneity according to age, sex, and obesity criteria [21].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis revealed that a lower DPI decreases the risk of overweight/obesity by 19% (95% confidence interval [8]: 0.74-0.90) [21]. However, the results demonstrated significant heterogeneity according to age, sex, and obesity criteria [21].…”
Section: Introductionmentioning
confidence: 99%